Kontrowersje związane z reklamowaniem leków. Analiza porównawcza Polski i Stanów Zjednoczonych - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2016)
For many years, the subject of aggressive marketing campaigns conducted by pharmaceuticalcompanies has been raised in Poland. Drug ads are everywhere, on television,the radio, magazines and on the Internet. Therefore, it is extremely importantis to ensure both their legal and ethical dimension.In my article I will present the differences between direct-to-consumer advertisingof medicines in Poland and in the US. The dissimilarities result mainly fromdifferences in legislation. In Poland the law is much stricter than in the US. Forexample, in the United States companies are allowed to advertise prescription drugsdirectly to patients. In the whole of the European Union, and thus in Poland, it isstrictly prohibited.The article will present other regulations existing in Poland and in the UnitedStates and it will compare them. It will show examples of violations of the law andethics in the advertising of medicine in both countries. It will briefly outline thenegative consequences of unacceptable pharmaceutical marketing.